2022
DOI: 10.1097/cji.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Association of Baseline and Pharmacodynamic Biomarkers With Outcomes in Patients Treated With the PD-1 Inhibitor Budigalimab

Abstract: Budigalimab, a novel anti-PD-1 monoclonal antibody, demonstrated efficacy and biomarker pharmacodynamics in patients with head and neck squamous cell carcinoma (HNSCC) or non-small cell lung cancer (NSCLC) consistent with those reported by other PD-1 inhibitors. Herein are presented additional outcomes of biomarker analyses from the phase 1 study of budigalimab monotherapy in patients with HNSCC and NSCLC (NCT03000257). PD-1 inhibitor naive patients with advanced HNSCC (n = 41) or NSCLC (n = 40) received budig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(134 reference statements)
1
8
0
Order By: Relevance
“…Most studies have focused on the frequency of immune cells in blood or tumor-infiltrating lymphocytes (TILs) and served as biomarkers of prognosis (51-53). Liu C, et al reported that the percentage of CD4 + Tn and Tm in peripheral blood are prognostic indicators for patients with NSCLC (54)(55)(56). However, the "Tn" of these researches was a mixture of Tn and Tscm due to not using CD95 monoclonal antibodies to discriminate Tscm from Tn according to the methods of the papers (57), while Tn and Tscm in our research had distinguished by CD95 monoclonal antibody.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Most studies have focused on the frequency of immune cells in blood or tumor-infiltrating lymphocytes (TILs) and served as biomarkers of prognosis (51-53). Liu C, et al reported that the percentage of CD4 + Tn and Tm in peripheral blood are prognostic indicators for patients with NSCLC (54)(55)(56). However, the "Tn" of these researches was a mixture of Tn and Tscm due to not using CD95 monoclonal antibodies to discriminate Tscm from Tn according to the methods of the papers (57), while Tn and Tscm in our research had distinguished by CD95 monoclonal antibody.…”
Section: Discussionmentioning
confidence: 53%
“…The "Tn" in these researches was completely different from the "Tn" of our manuscript. Meanwhile, this researches only analyzed the memory CD4 + and CD8 + T cells but did not fully analyze the subsets of memory cells, including Tscm, Tcm, Tem, and Tte (30,(54)(55)(56). More importantly, these studies did not analyze further the prognostic impact of each AC of the Tn/Tm subpopulation on patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a higher ORR (33.9% vs. 11.1%, p = 0.003) and disease control rate (DCR; 80.6% vs. 34.9%, p < 0.001) were also reported in patients with low IL-6 before treatment. In a recent study by Lambert and colleagues, low pre-treatment serum IL-6 associated with prolonged PFS ( p = 0.011) in a univariate analysis of the anti-PD-1 inhibitor budigalimab in patients with advanced NSCLC ( n = 40) or head and neck squamous cell carcinoma (HNSCC; n = 41) [ 28 ]. In another study using similar plasma cutoffs, a low baseline concentration of plasma IL-6 (< 11.150 pg/ml) associated with longer PFS ( p = 0.0142) following anti-PD-1 therapies in stage III-IV patients with NSCLC [ 29 ].…”
Section: Circulating Levels Of Cytokines and Soluble Factorsmentioning
confidence: 99%
“…Several studies ( n = 8) involving 634 patients have reported on the association between peripheral CD4 + (Table 4 ) and CD8 + (Table 5 ) T lymphocytes at baseline and response of NSCLC patients to ICI. Specifically, higher levels of lymphocytes, including higher percentage and count of total T cells, percentage of Ki67 + CD8 + T cells and natural killer (NK) cell count prior to treatment with the anti-PD-1 inhibitor budigalimab were associated with improved clinical response and longer PFS in a phase I trial that included 40 patients with advanced NSCLC [ 28 ]. Miao et al reported similar findings, with higher baseline CD4 + T cell counts with a memory phenotype (lacking expression of CD45RA, > 311.3 × 10 6 cells/L), associating with longer PFS ( p < 0.001) [ 69 ].…”
Section: Circulating Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation